Stone fruits: growth and nitrogen and organic acid metabolism in the fruits and seeds—a review - Famiani, Franco (2020)
Fil: Fil: Famiani, Franco. Università degli Studi di Perugia. Dipartimento di Scienze Agrarie, Alimentari e Ambientali; Italia.